The Influence of Social Media on Language and Vocabulary Learning: A Case Study at Paktia University - Sial, Sayed Rahman; Haqiqat, Habibullah; Waseel, Mohammad Wali (Randwick International of Education and Linguistics Science Journal, 2026)
Social media is now a common way for people of all ages to communicate. Social media sites like Facebook, YouTube, and Twitter have been used by educational institutions more and more as learning tools to interact with students and spread knowledge, in addition to being used for general communication. Social media's broad use has sparked debate over how useful it is as a teaching and learning tool. This study looks into how social media affects students' learning of English vocabulary in public and private institutions in Malaysia. Additionally, it investigates how social media affects students' motivation to acquire language skills. The study also looks at how these platforms affect language learning results, both positively and negatively. A questionnaire was used to gather data, and SPSS software was used for quantitative analysis. The findings indicate that social media fosters increased interest in language learning among English language learners.